Understanding of nitrogen fixation electro catalyzed by molybdenum–iron carbide through the experiment and theory. (February 2020) - Qin, Binhao; Li, Yuhang; Zhang, Qiao; Yang, Guangxing; Liang, Hong; Peng, Feng
Abstract: The electrochemical method is considered being a sustainable alternative to the industrial Haber-Bosch process (150–350 atm, 350–550 °C) because it can produce ammonia (NH3 ) from nitrogen (N2 ) and water (H2 O) at room temperature and pressure. However, since the N≡N triple bond in N2 is one of the strongest bonds in nature, it requires a more negative potential for N2 reduction, which often leads to violent hydrogen evolution reaction (HER) in aqueous electrolysis systems. Therefore, it is a great challenge for the electrocatalytic N2 reduction reaction (ENRR) to find catalysts that can reduce the energy barrier of N2 fixation and inhibit the HER. Herein, inspired by the Mo–Fe site in the biological nitrogenase, we found that the catalyst containing Mo3 Fe3 C active material has excellent N2 -fixing catalytic performance and can effectively inhibit the HER. At −0.05 V vs RHE, the Faraday efficiency (FE) of ENRR was as high as 27.0%. In addition, we innovatively used the Fourier-transformed alternating current voltammetry (FTACV) to explore the electron transfer process in ENRR, indicating that Mo3 Fe3 C is more conducive to reducing N2 at low potential. According to density functional theory (DFT) calculations, compared with Mo2 C and Fe3 C, Mo3 Fe3 C is more helpful in promoting N2 activation and hydrogenation. Due to the synergistic effect of the Mo–Fe site, N2 hydrogenation needs to overcome a lower energy barrier in potential-determining step (PDS). Our research extends the knowledge into bimetallic active sites in ENRR and provides a new insight for the subsequent synthesis of high selectivity catalysts. Graphical abstract: Image 1 Highlights: A new Mo3 Fe3 C catalyst for electrocatalytic N2 reduction reaction (ENRR) is reported. The prepared catalyst shows a faraday efficiency of 27% for N2 reduction to NH3 . Electron transfer in ENRR is explored by Fourier-transformed alternating current voltammetry. The synergistic effect of the Mo–Fe site is revealed by density functional theory calculations.